STRATEGI PEMBELAJARAN ORANG TUA DALAM MENGEMBANGAN KREATIVITAS ANAK SELAMA LIBURAN SEKOLAH PADA MASA COVID 19 - Zulfitria Zulfitria; ahmad Susanto; Sriyanti Rahmatunnisa; Zainal Arif; Tyasti Aryandini (Universitas Muhammadiyah Jakarta, 2023)
The purpose of this study was to find out what learning strategies were used by parents in developing children's creativity at home during school holidays during the Covid 19 period. The current condition, namely the Covid-19 pandemic, parents play a very central role, accompanying their sons and daughters studying at home. The role of parents during a pandemic can cause various things that can be positive or negative. What are the parents' strategies for discovering new things so that children can play and learn and be creative at home in a pleasant atmosphere, so that children can refrain from playing outside the home without parental assistance to prevent the spread of Covid-19. This study uses a qualitative method with a qualitative descriptive approach. Retrieval of data with observation techniques, interviews and documentation. This research was conducted in June 2022 during school holidays. With three elementary school-aged children as research subjects. From the results of the study it can be seen that parents must have good learning strategies so that children during school holidays continue to gain other knowledge and become creative children.